Effect of organic modifiers and silicate type on filler dispersion, thermal, and mechanical properties of ABS-Clay nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Journal of Applied Polymer Science, 2008)
Acrylonitrile-butadiene-styrene (ABS)-clay composite and intercalated nanocomposites were prepared by melt processing, using Na-montmorillonite (MMT), several chemically different organically modified MMT (OMMT) and Na-laponite clays. The polymer-clay hybrids were characterized by WAXD, TEM, DSC, TGA, tensile, and impact tests. Intercalated nanocomposites are formed with organoclays, a composite is obtained with unmodified MMT, and the nanocomposite based on synthetic laponite is almost exfoliated. An unintercalated nanocomposite is formed by one of the organically modified clays, with similar overall stack dispersion as compared to the intercalated nanocomposites. T, of ABS is unaffected by incorporation of the silicate filler in its matrix upto 4 wt % loading for different aspect ratios and organic modifications. A significant improvement in the onset of thermal decomposition (40-44 degrees C at 4 wt % organoclay) is seen. The Young's modulus shows improvement, the elongation-at-break shows reduction, and the tensile strength shows improvement. Notched and unnotched impact strength of the intercalated MMT nanocomposites is lower as compared to that of ABS matrix. However, laponite and overexchanged organomontmorillonite clay lead to improvement in ductility. For the MMT clays, the Young's modulus (E) correlates with the intercalation change in organoclay interlayer separation (Delta d(001)) as influenced by the chemistry of the modifier. Although ABS-laponite composites are exfoliated, the intercalated OMMT-based nanocomposites show greater improvement in modulus. (C) 2008 Wiley Periodicals, Inc. J Appl Polym Sci 110:2374-2383, 2008
Keywords: clay; filler; mechanical; structure characterization; styrene-butadiene

Effect of blend composition and organoclay loading on the nanocomposite structure and properties of miscible poly(methyl methacrylate)/poly(styrene-co-acrylonitrile) blends - Tiwari, Rajkiran R.; Natarajan, Upendra (Polymer Engineering and Science, 2011)
Organically-modified montmorillonite clay nanocomposites of poly(styrene-co-acrylonitrile) (SAN), poly(methyl methacrylate) (PMMA) and SAN/PMMA miscible blend are investigated. Structure characteristics at the nanoscale and microscale and thermal and tensile properties are studied as a function of polymer blend composition and filler loading fraction. Blend miscibility and T(g) are unaffected by up to 10% by wt. organoclay. Thermal degradation stability increases with SAN content and exhibits an optimum value of clay loading. Stiffness shows significant improvement. Tensile strength and elongation-at-break suffer as a result of nanocomposite formation. Modulus shows a maximum enhancement of 57% (5 +/- 0.06 GPa at 10 wt% filler, 20/80 SAN/PMMA) and varies linearly with clay fraction for all compositions of matrix phase. Predictions of Halpin-Tsai composite model are in excellent agreement with the experimental behavior over full range of polymer blend composition. Fundamental aspects of a polymer blend-clay nanocomposite are clarified, such as lack of additional synergy between clay platelets and matrix, and tensile ductility reduction, compared with polymer-clay system. POLYM. ENG. SCI., 51:979-991, 2011. (C) 2011 Society of Plastics Engineers

Effect of organic modification on the intercalation and the properties of poly(phenylene oxide)/polystyrene blend-clay nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Journal of Thermoplastic Composite Materials, 2013)
Nanocomposites prepared by the dispersion of unmodified and organically modified montmorillonite (MMT) clay into poly(2,6-dimethyl phenylene oxide)/polystyrene miscible blend in the range of 2-10 wt% clay were investigated by wide-angle x-ray diffraction, transmission electron microscopy, differential scanning calorimetry, thermogravimetric analysis and tensile mechanical tests. The systems based on unmodified sodium MMT (Na+MMT) as well as Cloisite 20A, Cloisite 30B and Cloisite 10A organically modified clays showed polymer intercalation. The glass transition temperature (T-g) value was not affected by the volume fraction of clay and chemical nature of the organoclay. The thermal degradation stability of nanocomposites is found to be only slightly better than that of the blend matrix. A percolation threshold of around 4 wt% organoclay loading is observed. An improvement of 35% relative to unfilled polymer blend matrix is observed for the modulus, for Cloisite 20A nanocomposite containing 2 wt% organoclay. The observed modulus improvement with significant retention of elongational tensile strength and tensile ductility in case of unmodified Na-MMT and Cloisite 30B nanocomposites appears promising. The modulus prediction using Halpin-Tsai model is found to be closer to the experimental data when MMT volume fraction rather than the organoclay volume fraction is used.
Keywords: filler; interface; interphase; mechanical properties; Nanostructures; Polymer-matrix composites